Cipher Plague: Decoding the Enigma of Viral Code and Cyber Threats - Syed Talal Musharraf ,; Muhammad Hamza Khan,; Salman Asghar,; Muhammad Zulkifl Hasan,; Muhammad Zunnurain Hussain,; Muhammad Atif Yaqub, (Dialogue Social Science Review (DSSR), 2025)
Encrypting viruses are computer viruses that, if not identified, can cause serious problems. For routine activities, the whole world depends on computer frameworks. Encoding viruses are thought to be among the most dangerous viruses because, once infected, they may begin scrambling the basic and secret records in general and documents saved on your PC or PC, leaving the papers ineffective and unclear, or they may be erased, causing information misfortune or a programmed processing plant reset, which can involve the cancellation of all records and the entirety of the essential data. Modern encrypted viruses have emerged as strong enemies in the fast-developing environment of cybersecurity threats, creating significant challenges to computer systems and networks worldwide. This research study examines the spreading techniques of these complex viruses, the potential dangers they offer, and the countermeasures put in place to prevent their destructive influence.